MIGRATION, DEMOGRAPHIC TRANSITION, AND THE IDENTITY QUESTION IN ASSAM - Islam, Saiful (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The history and politics of Assam have been deeply shaped by migration and the population changes that come with it. Right from the pre-colonial period people have been moving into Assam from other parts of India and from across the border. This movement has created both opportunities and tensions. At the same time, Assam’s population has been changing naturally through processes like high birth and low death rates, better health care, and lake of education. Together, migration and demographic change have influenced how different groups think about their identity, culture, and rights. This article looks at three issues: firstly, the main reasons and periods of migration into Assam, secondly, how population of Assam has changed over time, and thirdly, how these changes are linked to identity politics, especially around language, land, and citizenship. The study is based on census and survey data, historical records, relevant articles, books and interviews with community members. It argues that the identity question in Assam cannot be solved only through laws and borders. Instead, it requires development, fair documentation, and dialogue between communities.